2002
DOI: 10.1101/lm.46102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stress and Hippocampal NMDA Receptor Antagonism on Recognition Memory in Rats

Abstract: Exposures to uncontrollable stress have been shown to alter ensuing synaptic plasticity in the hippocampus and interfere with hippocampal-dependent spatial memory in rats. The present study examined whether stress, which impairs hippocampal long-term potentiation (LTP), also affects (nonspatial) hippocampal-dependent object-recognition memory, as tested on the visual paired comparison task (VPC) in rats. After undergoing an inescapable restraint-tailshock stress experience, rats exhibited markedly impaired rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
168
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(190 citation statements)
references
References 83 publications
16
168
2
4
Order By: Relevance
“…These findings are relevant since the novel object recognition task in rodents is a nonspatial, nonaversive memory test, in contrast to our previous reports (21,22). In addition, the object recognition task has also been increasingly used as a powerful experimental tool to assess drug effects on memory and to investigate the neural mechanisms underlying learning and memory (24,25,(32)(33)(34)(35).…”
Section: Discussioncontrasting
confidence: 50%
“…These findings are relevant since the novel object recognition task in rodents is a nonspatial, nonaversive memory test, in contrast to our previous reports (21,22). In addition, the object recognition task has also been increasingly used as a powerful experimental tool to assess drug effects on memory and to investigate the neural mechanisms underlying learning and memory (24,25,(32)(33)(34)(35).…”
Section: Discussioncontrasting
confidence: 50%
“…Three way ANOVA for percent asymmetry with factors of Group, Brain Region and Time revealed a significant main effect for Group (F [1,264] = 154.96, P < 0.001) and Region (F [10,264] = 7.46, P < 0.001) but no main effect for Time (F [1,264] = 0.19, P = 0.657). A significant interaction occurred between Group and Brain Region (F [1,11] = 11.96, P < 0.001), where the most impacted regions were the primary motor cortex followed by the primary sensory and frontal cortices (F [3,11] =45.1, P<0.001). Two-way repeated measures analysis of percent asymmetry data from only cannulated animals that completed both scans were performed for each region, where factors were Group and Time.…”
Section: [ 18 F]fdg Micropet Resultsmentioning
confidence: 99%
“…Many cortical brain regions are pivotal to the formation of memories and brain plasticity [3,7,29] and intracranial surgery usually involves cortical regions even if the target is subcortical. For example, a surgical implant targeting the striatum passes through the motor and sensory cortices of the rat, and we have shown that these areas as well as distal cortical areas show a persistent metabolic decline long after the cannulation.…”
Section: Introductionmentioning
confidence: 99%
“…A preference for the novel object during the choice phase was assessed using one-sample t-tests to determine whether time spent with the novel object differed significantly from the chance value of 15 s (Baker and Kim, 2002;Frick and Gresack, 2003). This type of t-test was used because time spent with the novel object is not independent from time spent with the familiar object, as the total time exploring must equal 30 s. For the same reason, one-sample t-tests were used to determine whether time spent with the northwest object during the sample phase differed significantly from 15 s.…”
Section: Discussionmentioning
confidence: 99%